Desenvolvimento e validação de gel de carboidratos à base de água de coco em pó para reposição energética de atletas - Felipe, Thiago Renee (2019)
The availability and metabolism of carbohydrates can influence both processes of (neurological) and peripheral (muscle) fatigue. Performance exercises can be hampered by reducing carbohydrate levels, thus decreasing muscle arousal process. Facing this problem, this study aimed to develop and validate a carbohydrate gel based on powdered coconut water (NATUGEL) for athlete’s energetic replacement. Presented as specific objectives: (1) To develop a gel of carbohydrates based on powdered coconut water according to the norms suggested by ANVISA; (2) Carry out the physical-chemical description of the carbohydrate gel based on coconut water; (3) To validate the use of coconut water-based carbohydrate gel in athletes in preworkout, post-workout and 24 and 48 hours post-workout through: (a) the effect of subjective perception of effort on different forms of gel supplementation used; and (b) the sharp post-training recovery response in different forms of gel supplements used. The study consisted of 14 ultra-marathon athletes, age group between 30 and 50 years old, in a pre-competitive training situation. The design was cross-over. Participants were divided into two groups: G1 - Control Group (commercial gel ingestion), and G2 - Group Treatment (ingestion gel based on powdered coconut water). The training session was held at the athletic runaway of Center for Integrated Child Care (CAIC-RN) and blood samples were collected in loco, kept in appropriate containers and sent to lab analysis. The evaluation from the Subjective Effort Perception (PSE) was performed through the application of the OMNI Walk / Run Scale (scores of 0-10). A trust level of 95% was maintained in all analyzes. According to the results obtained in this study, it was concluded that: (a) The composition of the bio-product NATUGEL fits perfectly into the legislation of "Food for Athletes" inside the category of "Carbohydrate Gel", presenting quantity of metabolizable carbohydrates following the requirements and assisting in recovery of normal muscle function after strenuous exercise; (b) The NATUGEL bio-product, when consumed by athletes during endurance exercise (considered as strenuous), it maintains glycemic levels, attenuates PSE and acts positively by accelerating postworkout muscle recovery; and (c) In addition as a rich carbohydrate product, it may also be used in electrolyte replacement. Its 100% origin vegetable and its components of high nutritional value are presented as a differential market at Food category for Endurance Athletes.